Influence of Messa di Voce speed on vocal stability of professionally trained singers. - Marie Köberlein; Jonas Kirsch; Michael Döllinger; Matthias Echternach (PLoS ONE)
Introduction Messa di Voce (MdV) is a challenging task for singers, requiring an even modulation of sound pressure level (SPL) on a stable pitch. This study concentrates on the effects of fast or slow task-speed on voice stability parameters, and the associated laryngeal behavior. The focus is set on professionally trained singers. Material and methods Ten professionally trained, healthy singers (5 female, 5 male) were asked to perform MdV exercises, i.e., a gradual increase and decrease of SPL, on the vowel [i:] on a stable fundamental frequency (fo ≈ 247 Hz for females and fo ≈ 124 Hz for males). First, each phase, i.e., increasing or decreasing SPL, should take 3 s. Second, each phase should take 1 s. The tasks were recorded by high-speed videolaryngoscopy (HSV), electroglottography, and audio signals. The following parameters were calculated and compared to the sound pressure level (SPL) curve: Electroglottographic (EGG) and Glottal Area Waveform (GAW) Open Quotients (OQEGG, OQGAW), Closing Quotient (ClQGAW) relative to start, Relative Average Perturbation (RAPAudio/EGG/GAW), and Sample Entropy (SE EGG). Results In most subjects, no correlation of vibrato and SPL course was detected. Instabilities with higher SEEGG occurred at the start/end of the slow task, but not around the SPL apex. Generally, negative correlations of SPL to OQGAW, ClQGAW and RAPAudio were present. RAPEGG and RAPGAW were not significant. In five subjects the decreasing phase of the slow task was 1-2 s longer. The majority of subjects ended the tasks softer than they had started. Conclusion RAP values and SE suggest high laryngeal stability in professional singers. Vibrato did not play a role in the variation of SPL in the presented cohort. The data suggest that SPL variation is mainly controlled on vocal fold level rather than by vocal tract resonances.